Retirement Preparedness in Saudi Arabia - Diaw, Alassane (International Journal of Economics and Financial Issues, 2017)
This paper studies the behavior towards retirement of a sample of workers from Al Jouf Region in Saudi Arabia. This is, in particular, to identify socio-economic factors put forward in preparing for retirement. Data collected via questionnaires are analyzed using factor analysis. Beyond the general perception which associates retirement to something negative, the concepts of freedom, family connectedness and leisure are frequently highlighted by respondents. The results show the lack of financial planning despite the possible deterioration of their economic situation worried by most respondents. Moreover, investment in financial products attracts future retirees in spite of their lack of knowledge of the related risks. Keywords: retirement planning, savings, risk and expectations JEL Classifications: D14, J26